The relationship between work-life balance, job satisfaction and job performance - Navanitham, Thangarasi Mathaliar (2016)
This study examines the relationship between work-life balance and job performance while job satisfaction play role as mediator. As for that, a framework was developed and proposed four hypotheses. A total of 147 respondents consist of academician from three public universities at Northern Region namely as UUM, UiTM Merbok and UniMAP was participated in this study which conducted online through Google Documented Questionnaire. The data obtained for this study was analyzed by using SPPS Version 22. A number of statistical analysis techniques were conducted in order to achieve the final mean for this study. The study hypotheses were tested using Pearson correlation and multiple regression analysis. The results supported and accepted all the proposed hypotheses for this study. Through Pearson correlation analysis it show all the variables is positively correlated to each other. However, by processing another step using Multiple Regression it confirm that all the variables have significant and positive relationship to each other. In addition, job satisfaction also had been proved as full mediation in the relationship between work-life balance and job performance. In conclusion, this study provides further information and understanding on relationship possess between variables that is work-life balance, job satisfaction and job performance. Therefore, it’s believed that practitioners will get benefit and additional knowledge from this study.